Ort und Zeit Filmische Heterotopien von Hochbaum bis Tykwer - Wedel, Michael (Cinepoetics Essay, 2020)
Like any story, the story of film doesn't just unfold in time it is also linked to the locations in which it is inscribed. The filmic poetics that governed this process at different points in the history of cinema are the subject of this book. Using examples ranging from the 1930s to the 1990s, it explores the social and political horizons of heterotopic conceptions of space in German film.